Encyclopedia of stakeholder management - Rendtorff, Jacod D.; Bonnafous-Boucher, Maria (Elgar encyclopedias in business and management series, 2023)
"This Encyclopedia provides a comprehensive overview of the most important concepts of stakeholder theory and management in business and public administration. It identifies that stakeholders are essential for value-creation in democratic societies. Featuring 81 entries from a wide range of expert contributors, this Encyclopedia presents an accessible overview of key ideas as well as highlighting current issues and emerging areas of study. Topics covered include business ethics, corporate social responsibility, sustainability, corporate governance, business legitimacy and good corporate citizenship, to reveal how stakeholders are crucial to both business and society. The Encyclopedia of Stakeholder Management will be a valuable resource for academics and students in corporate social responsibility, strategic management and organizational theory. It will also be useful for practitioners in business, NGOs and public administration who work with stakeholders and stakeholder theory. Key Features: - Over 80 entries - Accessible explanations of key concepts - Contributions by recognized stakeholder scholars - Integration of stakeholders with business ethics and corporate social responsibility"--